Analyzing 2017 Indonesia Demographic Health Survey: Knowledge, Socio-demographics, and HIV/AIDS Prevention among Housewives - Indrawati, Fitri; Rahmadani, Haeda Dyah Masna; Nurjannah, Fani Eka (Jurnal Kesehatan Masyarakat, 2024)
The spread of HIV/AIDS in Indonesia is increasing and dominated by housewives. This study aims to analyze the knowledge and sociodemographics that influence HIV/AIDS prevention behavior among housewives in Indonesia through data from the 2017 Indonesian Demographic and Health Survey (IDHS 2017), the data used were women of childbearing age (15-49 years) with 12,445 samples. Cross-sectional study design with Chi-square test on bivariate analysis and logistic regression test on multivariate test. The results showed that there was a significant relationship between knowledge and HIV/AIDS prevention behavior. Woman who had better knowledge about HIV/AIDS tended to use condoms more often and take HIV tests and had positive attitudes towards safe sex also positively correlated with better prevention behavior. Regression results also revealed that sociodemographic factors such as knowledge, age, latest education, economic status, and place of residence had a significant impact on HIV/AIDS prevention behavior. This suggests the need for a diverse approach in designing prevention education programs that suit the characteristics of housewives.